Pregnant women with morbid obesity: pregnancy and perinatal outcomes - Yunusova Zarnigor Maqsadovna (Genius Journals, 2023)
Prevention of obesity in women of reproductive age is widely recognised to be important both for their health and for that of their offspring. Weight-control interventions, including drug treatment, in pregnant women who are obese or overweight have not had sufficient impact on pregnancy and birth outcomes, which suggests that the focus for intervention should include preconception or post-partum periods. Further research is needed into the long-term effects of nutritional and lifestyle interventions before conception. To improve preconception health, an integrated approach, including pregnancy prevention, planning, and preparation is needed, involving more than the primary health-care sector and adopting an ecological approach to risk reduction that addresses personal, societal, and cultural influences. Raising awareness of the importance of good health in the period before pregnancy will require a new social movement: combining bottom-up mobilisation of individuals and communities with a top-down approach from policy initiatives. Interventions to reduce or prevent obesity before conception and during pregnancy could contribute substantially to achievement of the global Sustainable Development Goals, in terms of health, wellbeing, productivity, and equity in current and future generations
Keywords: obesity; morbid obesity; pregnancy complications; perinatal outcomes